A report on practice-in-industry conducted at the Modesto Cruz brackishwater fishpond in Binuangan, Obando Bulacan - Castillo, Carmen Biagtan
Courses in the applied sciences such as Fisheries require thorough exposure and application in their respective fields. The practicum requirement of the Fisheries degree sees to it that the student is adept involving himself in actual field conditions aside from the theoretical atmosphere of the classroom. In effect, the student is able to apply with considerable results the acquired theories in the inland fisheries course to the betterment of the fishing industry. This practicum report involves important methods in the culture of milkfish primarily in brackish water including the suggested reinforcements.